ChemInform Abstract: Ammonothermal Synthesis and Characterization of Cs2[Zn(NH2)4]. Issue 52 (6th December 2016) - Richter, Theresia M. M.; Alt, Nicolas S. A.; Schluecker, Eberhard; Niewa, Rainer
Abstract: Single crystals of the title amidozincate of several centimeters in dimensions are grown under ammonothermal conditions in the cold temperature zone of an autoclave using Zn powder and CsNH2 in a 1:2 molar ratio (stainless steel autoclave, 523→≈423 K, 155 MPa, 12 h).